PENGARUH BRANDING DAN PEMASARAN KREATIF PRODUK BAION (TALI PLAT MEREK MACAN) TERHADAP PENDAPATAN PEREMPUAN DI DESA PEMATANG PANJANG DENGAN KEARIFAN LOKAL SEBAGAI VARIABEL INTERVENING - Saputra Ompusunggu, Josua; Darmansyah, Ilham; Arfah, Yenni; Nursaimatussadiyya, Nursaimatussadiyya (Penerbit Lafadz Jaya, 2026)
This study aims to analyze the influence of branding and creative marketing on the income of female artisans of Baion products (Macan brand woven plastic rope) in Pematang Panjang Village with local wisdom as a moderating variable. The low and fluctuating income of female artisans is the background of this study, due to weak branding and creative marketing strategies despite Baion products having strong cultural potential. This quantitative study used a saturated sample of 61 female artisan respondents. Data was collected through a 5-point Likert scale questionnaire, observation, and documentation, then analyzed using SmartPLS 3.0 software. The results showed that branding had a positive and significant effect on local wisdom and women's income. Creative marketing had a positive and significant effect on local wisdom but did not have a significant direct effect on income. Local wisdom had a positive and significant effect on women's income and successfully mediated the effect of branding and creative marketing on income. The research model showed very good predictive relevance with an R-squared value of 0.928 for local wisdom and 0.943 for women's income. This research proves the importance of integrating local wisdom into creative branding and marketing strategies to improve the economic welfare of female artisans in rural areas.